2020
DOI: 10.1186/s12902-020-00625-1
|View full text |Cite
|
Sign up to set email alerts
|

Flash glucose monitoring system was applied to cortisol treatment for a patient with congenital adrenal hyperplasia and 17α-hydroxylase deficiency

Abstract: Background Congenital adrenal hyperplasia (CAH) with 17α-hydroxylase deficiency is a rare disease; patients often require lifetime cortisol treatment. In this case report, we presented a patient with CAH and 17α-hydroxylase deficiency, who was previously misdiagnosed as having primary aldosteronism. Furthermore, the flash glucose monitoring system (FGMS) was used to ascertain a suitable cortisol therapeutic regimen for this patient. Case presentation A 29-year-old woman presented with sex dysgenesis, hyperte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
0
0
Order By: Relevance
“…In a case report by Xiang et al, steroid dose and glucose levels were investigated using CGM in a 29-year-old patient with CAH. They observed that blood glucose levels during the night and fasting periods decreased considerably before glucocorticoid administration, while they increased significantly postprandially after cortisol treatment ( 8 ). Cortisol deficiency increases insulin sensitivity, activates gluconeogenesis, decreases glycogenolysis, and enhances the activity of counterregulatory hormones such as glucagon, epinephrine and other catecholamines ( 9 ).…”
Section: Discussionmentioning
confidence: 99%
“…In a case report by Xiang et al, steroid dose and glucose levels were investigated using CGM in a 29-year-old patient with CAH. They observed that blood glucose levels during the night and fasting periods decreased considerably before glucocorticoid administration, while they increased significantly postprandially after cortisol treatment ( 8 ). Cortisol deficiency increases insulin sensitivity, activates gluconeogenesis, decreases glycogenolysis, and enhances the activity of counterregulatory hormones such as glucagon, epinephrine and other catecholamines ( 9 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, there are currently no prospective studies on glucose profiles of children and adolescents with CAH. Xiang et al ( 16 ) reported an adult patient with CAH where cortisol dosage adjustment was facilitated by the use of a flash glucose monitoring system.…”
Section: Introductionmentioning
confidence: 99%